2022
DOI: 10.3390/ma15176114
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Measurement of Cyclic Plastic Zone and Internal Strain Response of Q&P Steel near Fatigue Crack Tip Region Based on Micro-DIC

Abstract: The shape and internal dynamic response characteristics of the plastic zone near the fatigue crack tip region, especially the cyclic plastic zone (CPZ), are the main factors affecting the fatigue crack initiation and propagation behaviors of ductile metal materials. The existing methods for characterizing the CPZ have some problems, which include the complexity of the process, the difficulty of achieving in situ measurement, and the inability to characterize the dynamic response in the CPZ during the crack pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…One side of the specimen was polished to a diffuse surface to measure the crack length, and the other side was sprayed with a professional speckle tool to create a uniform microscopic speckle for the analysis of the fatigue crack tip deformation fields. The preparation of specimen and crack images with crack tip speckle images were shown in Gao et al 30 The orientation distribution and metallographic distribution of the material are shown in Figure 1B,C. SEM characterization experiments show that the Q&P980 steel material mainly comprised mostly ferrite (F) and martensite (M) matrix and a small amount of RA.…”
Section: Materials and Specimensmentioning
confidence: 97%
See 1 more Smart Citation
“…One side of the specimen was polished to a diffuse surface to measure the crack length, and the other side was sprayed with a professional speckle tool to create a uniform microscopic speckle for the analysis of the fatigue crack tip deformation fields. The preparation of specimen and crack images with crack tip speckle images were shown in Gao et al 30 The orientation distribution and metallographic distribution of the material are shown in Figure 1B,C. SEM characterization experiments show that the Q&P980 steel material mainly comprised mostly ferrite (F) and martensite (M) matrix and a small amount of RA.…”
Section: Materials and Specimensmentioning
confidence: 97%
“…In 2022, our research group proposed a high-precision in situ measurement method of crack tip deformation fields using micro sub-image stitching and matching DIC method and realized the measurement of crack tip deformation field evolution in the whole FCG process without unloading and stopping the tester. 29 The evolution laws of fatigue crack tip deformation fields and cyclic plastic zone under constant load and the closing effect of short fatigue crack in Q&P steel 30,31 were studied based on the proposed method, which supply a strong experimental basis for studying the crack tip deformation and growth behaviors under variable amplitude loads.…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, DIC possesses the advantages of simple optical path, good environmental adaptability, wide measurement range and high degree of automation, and has been widely used in full-field non-contact testing of mechanical properties of materials [21,22].…”
Section: Principle Of the Two-dimensional Digital Image Correlation M...mentioning
confidence: 99%
“…At present, the methods for characterizing the fatigue behavior of the components mainly include stress/strain-based methods, fracture mechanics methods, and continuum damage mechanics (CDM) methods [10][11][12][13][14][15][16][17][18][19][20]. The stress/strain-based methods mainly include the stress-based life evaluation method, e.g., the Basquin equation and the strain-based life evaluation method, e.g., the Morrow method and the Manson-Coffin formula [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Whittaker et al [11] used the Walker strain method to study the effects of temperature and stress ratios on fatigue damage parameters, and the results showed that the Walker strain equation can better evaluate the fatigue damage of the nickel-based components in the range of 600-750 • C. The fracture mechanics method is mainly based on Paris' law [10][11][12][13][14][15][16]. The CDM-based methods are used to evaluate the fatigue damage of the component by calculating the damage parameters [17][18][19][20]. Kim et al [17] developed a fatigue life model based on CDM for predicting the fatigue life of nickel-based alloys under creep-fatigue interactions.…”
Section: Introductionmentioning
confidence: 99%